National Consensus or Social Anomaly?: On the Peculiarities of Mass Consciousness in "Post-Crimean" Russia. Issue 1 (2nd January 2016) - Byzov, Leontii L.
Abstract : The dynamics of mass consciousness in Russia, formed in the wake of the 2014 events in Ukraine and Crimea, testify to the consolidation and radicalization of the popular majority. The national consensus has shaped a high level of public optimism even in the face of deteriorating socioeconomic conditions. However, this process brings to the fore archetypal traits that in many ways run contrary to the modern desire for mass consumption, which in many ways is also contrary to social mobilization. This contradiction will affect the political process, if not in the short- then in the long term, and will significantly affect the sociopolitical situation, making it less stable than in the first decade of the present century.